Enhancing essential oil production in rosemary (Rosmarinus officinalis L.) with salicylic acid and methyl jasmonate and its relationship to spectral indices - Thussagunpanit Jutiporn; Chookoh Nittaya; Donsri Wariya; Tepkaew Teerapat; Mayong Amonrat; Boonkorkaew Patchareeya; Sreewongchai Tanee (Folia Horticulturae)
Rosemary is a widely used herb known for its diverse health benefits, attributed to its essential oil content. However, cultivating rosemary requires careful attention to environmental conditions, particularly in regions with unpredictable climates such as high temperatures. This study explored the potential of salicylic acid (SA) and methyl jasmonate (MeJA) to optimise rosemary cultivation, based on their impact on rosemary growth, physiological changes, and essential oil production. Rosemary plants were grown in an experimental field in Phetchabun province, Thailand. Shrubs were foliar-applied with SA or MeJA at 0, 0.01, 0.1, or 1 mM two times (5 months and 6 months, respectively, after transplanting). Growth parameters, photosynthetic pigments, spectral indices, and essential oil were estimated. Essential oil was extracted using steam distillation. Statistical analyses consisted of one-way Analysis of Variance (ANOVA) and Pearson’s correlation coefficient with significance set at p < 0.05. Based on the results, the application of specific concentrations of SA or MeJA significantly impacted growth, while there were no significant differences among photosynthetic pigments. However, the rosemary plants treated with 1 mM SA or 0.01 mM MeJA had higher R425 and R450 spectral indices than the control. Applying SA (1 mM) and MeJA (0.01 mM) enhanced the rosemary essential oil content. In addition, the essential oil contents in rosemary were highly correlated with changes in the R425 and R450 indices. In conclusion, SA and MeJA had impacts on the growth and essential oil content of rosemary. The R425 and R450 spectral indices can be further utilised to estimate the rosemary essential oil.